Selected clinical highlights from the 2010 ERS congress in Barcelona - Silva Robalo Cordeiro, Carlos Manuel da; Singh, S.; Herth, Felix; Ley, Sebastian; Chavannes, N. H.; Clini, E.; Cottin, V. (The European respiratory journal, 2011)
This article reviews a selection of presentations at the 2010 annual meeting of the European Respiratory Society held in Barcelona, Spain, which was the largest congress ever in the field of respiratory medicine. The best abstracts from the groups of the Clinical Assembly (Clinical Problems, Rehabilitation and Chronic Care, Imaging, Interventional Pulmonology, Diffuse Parenchymal Lung Disease, and General Practice and Primary Care) are presented in the context of the current literature.
First published online March 24, 2011
Gesehen am 12.04.2022